Highly Sensitive NH3 Sensors Using CVD and Epitaxial Graphene Functionalised with Vanadium(V) Oxide: A Comparative Study - Margus Kodu; Artjom Berholts; Tauno Kahro; Jens Eriksson; Rositsa Yakimova; Tea Avarmaa; Indrek Renge; Harry Alles; Raivo Jaaniso (Proceedings, 2018)
Exceptionally sensitive and selective graphene-based chemiresistive gas sensors were produced as a result of graphene functionalisation with a sub-nanometer V2O5 layer by using the method of pulsed laser deposition. Two different types of graphene were used—epitaxial graphene on SiC and CVD graphene on Si/SiO2—and both showed remarkable enhancement of sensing properties in terms of response and recovery speed, response magnitude and selectiveness towards NH3 gas. The epitaxial graphene-based sensor was demonstrating the highest relative response towards ammonia amounting to 80% for 0.1 ppm NH3.